Acceptance of a new non-invasive fetal monitoring system and attitude for telemedicine approaches in obstetrics: a case-control study - Mair, Katharina; Lapert, Florian; Nees, Juliane; Lempersz, Carlijn; Oei, S. Guid; Haun, Markus W.; Maatouk, Imad; Bruckner, Thomas; Sohn, Christof; Schott, Sarah (Archives of gynecology and obstetrics, 2018)
Reduction of maternal morbidity and mortality is a major worldwide objective anchored in the millennium goals of the United Nations. To improve fetal and maternal care, a constant attempt to discover groundbreaking technologies is ongoing. One approach is the enhancement of non-invasive fetal ECG devices. Most importantly, acceptance of new technologies by pregnant women is a prerequisite for successful implementation.
Gesehen am 23.04.2020